PEMETAAN PENGGUNAAN BAHAN AJAR PADA MATA PELAJARAN PRODUKTIF AKUNTANSI KELAS X DI SMK NEGERI 1 SURABAYA - YULIA AGUSTINA (Jurnal Pendidikan Akuntansi (JPAK), 2013)
This research aims are determining what materials are used, the reasons teachers using the and the feasibility of teaching materials used in accounting productive subjects of class 10th at SMKN 1 Surabaya . This research is descriptive. The data was collected by using a questionnaire and guiding interview. The analysis using qualitative descriptive and quantitative descriptive. The results show that the prime teaching materials are used in the accounting productive subjects of class 10th at SMK Negeri 1 Surabaya is the text book has created by Toto Sucipto and to be complete by many other books. Reasons teachers use the teaching materials such as suitability of conmpetency standart and basic competencies, teaching materials easily understood, cost of purchasingthe teaching materials more efficient, and the information which is provided up to date. Feasibility of teaching materials are based on feasibility criteria for Badan Standar Nasional Pendidikan (BSNP) that is looks from the contents component, the presentation component, the language component and the graph component, this teaching material are included in category "Feasible". Key Word : Teaching Materials, Productive of Accounting, Feasibility of Teaching Materials